Evaluating the Challenges Affecting Tourism Development in Gashaka Gumti National Park - Silas, Akafa Konde; Madaki, Kanati; Chibuma, Gani Saidu (Darul Yasin Al Sys, 2025)
This study evaluates the key challenges hindering tourism development in Gashaka Gumti National Park, Nigeria. Data were collected through 100 structured 5-point Likert scale questionnaires administered to park staff, with responses analyzed using IBM SPSS version 25 and descriptive statistics. Findings reveal that the continuous presence of enclave communities within the park poses a major threat to its sustainability, as livelihood activities such as farming, poaching, lumbering, mining, honey harvesting, open grazing, fishing, and bush burning negatively affect park development. Additional challenges identified include lack of cooperation from enclave communities, impacts of climate change, attacks on rangers, inadequate manpower, insufficient budgetary allocation, and poor ranger welfare. The study concludes that these challenges significantly constrain the park’s tourism potential and conservation efforts. It recommends increased resource allocation by the Federal Government of Nigeria, along with improved ranger welfare, stronger community engagement, and enhanced manpower capacity, to ensure more effective management and sustainable tourism development in Gashaka Gumti National Park.